2006
DOI: 10.1080/08916930600893709
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA class II DRB1, DPA1 and DPB1 polymorphism with genetic susceptibility to idiopathic dilated cardiomyopathy in Chinese Han nationality

Abstract: Although the aetiology of idiopathic dilated cardiomyopathy (IDC) remains unclear, many immunological abnormalities involving changes in cell-mediated and humoral immunity may be associated with cardiac impairment in IDC. Autoimmune mechanisms are likely to participate in the pathogenesis of at least a subgroup of IDC and components of the major histocompatibility complex may serve as markers for the propensity to develop immune-mediated myocardial damage. Human leukocyte antigen (HLA) class II genes, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…Specifically, HLA-DR4 is statistically associated with DCM based on retrospective studies [9092]. Other DCM-HLA-positive associations had been reported, mainly HLA-DR12, DR15, and DRB*0601, as well as negative associations (HLA-DR11, DQB1*0301) [9395]. …”
Section: 3 Specific Factors Triggering/predisposing Myocarditis Dementioning
confidence: 99%
“…Specifically, HLA-DR4 is statistically associated with DCM based on retrospective studies [9092]. Other DCM-HLA-positive associations had been reported, mainly HLA-DR12, DR15, and DRB*0601, as well as negative associations (HLA-DR11, DQB1*0301) [9395]. …”
Section: 3 Specific Factors Triggering/predisposing Myocarditis Dementioning
confidence: 99%
“…Previous evidence suggested that genetic susceptibility to IDC is linked to HLA class II alleles, particularly the HLA-DR4 seems to be associated with a high risk (23). However, results remain inconsistent and discrepant among different studied populations, such as HLA-DQA1*0501, HLA-DQB1*0303, and HLA-DPB1*0601 had been observed as a susceptible factor for the IDC in northern China (5,8), while in Mexican, HLA-DQB1*0301 and HLA-DQB1*0302 was found to be positively related to the IDC (7).…”
mentioning
confidence: 93%
“…A large number of genetic studies have been carried out and addressed that various candidate genes such as alleles of HLA-DP, HLA-DQ, and HLA-DR in HLA class II gene may predispose to the pathogenesis of IDC. These studies indicated that abnormal expression of the HLA class II on cardiac endothelium was one of important autoimmune features in IDC, especially HLA-DR4 antigen seems to be associated with a high risk (5)(6)(7)(8)(9).…”
mentioning
confidence: 98%
“…Previous studies have demonstrated that genes linked to HLA‐DR molecules may contribute to the aetiological process of cardiac and cerebral damage (Zou et al ., ; Liu et al ., ; Zhang et al ., ). A review on immunogenetic susceptibility of atherosclerotic stroke reported the occurrence of microbial interactions with MHC antigens, TcR, cytokines and a number of systemic markers in the formation of atherosclerotic plaque in brain leading to stroke (DeGraba, ).…”
Section: Discussionmentioning
confidence: 99%